Kinetics of ¹⁵³Sm oxabiphor in the blood of cancer patients undergoing complex therapy for bone metastasis - Dikiy, N.P.; Lyashko, Yu.V.; Medvedeva, E.P.; Bodnar, E.N.; Grushka, A.V.; Krasnoselsky, N.V.; Paskevich, O.N. (Вопросы атомной науки и техники, 2015)
Concentration ¹⁵³Sm in the blood of patients with bone metastasis after radionuclide therapy was determined. Considerable variation of the content of ¹⁵³Sm in blood of patients with various primary cancers from 10 to 65 Bq/ml is found. The effective half-life of ¹⁵³Sm in the blood of patients was estimated at more than 10 days during the course of the therapy. Визначено концентрацію ¹⁵³Sm у крові пацієнтів з метастазами в кістковій тканині після радіонуклідної терапії. Виявлено значну варіацію вмісту ¹⁵³Sm у крові для хворих з різними первинними захворюваннями, що склала від 10 до 65 Бк/мл. Оцінено період напіввиведення ¹⁵³Sm із крові пацієнтів у процесі терапії, що складає більш 10 днів. Определена концентрация ¹⁵³Sm в крови пациентов с метастазами в костной ткани после радионуклидной терапии. Обнаружена значительная вариация содержания ¹⁵³Sm в крови для больных с различными первичными заболеваниями, которая составила от 10 до 65 Бк/мл. Оценен период полувыведения ¹⁵³Sm из крови пациентов в процессе терапии, составляющий более 10 дней.